Pengaruh Kegiatan Ektrakurikuler Rohis Terhadap Pergaulan Islami Peserta Didik SMA Negeri 2 Singkep - Rahayu Mega Sari; Pauzi; Syamsul Ridwan (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to determine the effect of Rohis extracurricular activities on the Islamic association of students at SMA Negeri 2 Singkep. The method used is a quantitative method using formulas Product Moment/relationship test and using questionnaire data collection techniques. The research subjects were the deputy head of the school for student affairs and PAI subject teachers as well as administrators and members of the Rohis totaling 40 students. The object of research is the implementation of spiritual and Islamic behavior of students. The data analysis method used is a validity test, reliability test, and correlation test. The results of the study show that the implementation of Rohis has a significant effect on Islamic behavior. This is proven based on the results of the correlation product Moment between variable X (spiritual practice) and variable Y (Islamic behavior) has a correlation value of 0.483. Thus (value Pearson correlation of 0.483 then) it can be concluded that the degree of value relationship pearson correlation is at 0.40-0.599 which is a level of relationship that is moderate. Therefore the research hypothesis can be accepted and it can be concluded that there is a good and significant influence of Rohis extracurricular activities on the Islamic association of students at SMA Negeri 2 Singkep. By participating in this Rohis extracurricular activity, the level of Islamic association of students will be better with supportive family, school, and community environmental factors.